Workplace Dynamics and the Potential for Fraud: A Qualitative Study in the Government Sector - Daurrohmah, Eka Wirajuang; Suryani, Pesi; Riyani, Etik Ipda (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to assess employee perceptions of the work environment in the Bengkulu government sector and its impact on fraud potential, with the aim of developing effective fraud prevention strategies. This study used a qualitative descriptive methodology using semi-structured interviews with government employees in Bengkulu Province. Data were analyzed using content analysis, which offers insight into the nuances of the work environment and its potential relationship to fraud by exploring employees’ subjective experiences and perspectives. The study found that employee perceptions of the work environment in the Bengkulu government sector are related to fraud potential. A conducive work environment and effective internal control are important preventive measures. Factors such as workload, pressure, and leadership behavior significantly shape employee perceptions and influence the likelihood of fraudulent activity. The theoretical implications of this study emphasize the importance of a conducive and ethical work environment in reducing fraud. Practically, these findings highlight the need for policy makers and government administrators to implement stringent internal controls, foster a culture of integrity, and ensure a transparent and merit-based system to minimize fraud and enhance public trust.